Variation and spread of resistomes in swine manure, manure slurries, and long-term manure-fertilized soils - Jin, Lei; Chen, Shujuan; Kang, Runmin; Li, Chun; Yang, Shengzhi; Yang, Qiaohui; Zhao, Ke; Zou, Likou (Frontiers in Microbiology, 2025)
BackgroundApplication of swine manure to soils exacerbates environmental antimicrobial resistance (AMR). However, a comprehensive evaluation of anaerobic digestion’s (AD) mitigation potential against AMR and its influencing factors in swine manure-to-soil systems remains lacking.MethodsWe employed mass spectrometry, metagenomics, and whole-genome sequencing (WGS) to investigate the fate of antibiotics, metals, and antibiotic resistance genes (ARGs) across manures, slurries, and soils from eight pig farms.ResultsAnaerobic digestion reduced antibiotic and metal (except ciprofloxacin) content and risks in manure, but had limited effects on total ARG abundance, while increasing ARG network modularity. High-risk ARG abundance significantly increased from 404.7 in manure to 843.2 in slurries, with health-risk scores rising 1.88-fold during anaerobic digestion. Metagenomic analysis showed metal resistance gene (MRG) diversity and abundance decreased during anaerobic digestion, along with reduced ARG-MRG co-occurrence frequency, whereas mobile genetic element (MGE) diversity and ARG-MGE co-occurrence frequency increased. Escherichia coli was identified as the dominant ARG host. WGS of E. coli strains confirmed horizontal gene transfer (HGT) of nine ARGs (e.g., sul3 and blaTEM-1), and metagenomics suggested HGT of four ARGs (e.g., tet(M)) across different pathogens. Chromium concentrations, bacterial communities and MGEs were significantly associated with ARG profiles. Long-term slurry application resulted in elevated antibiotic, metal, and ARG concentrations in soils, with concomitant increases in high-risk ARGs and health risks.ConclusionThis study demonstrates AD’s limited effect on mitigating overall ARG abundance and highlights MGEs as critical drivers of ARG maintenance and dissemination from manure to soil process, guiding manure treatment optimization to reduce agricultural AMR risks.